2015
DOI: 10.4236/ojgas.2015.512028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HBs Antigen, and HCV and HIV Antibodies in a Young Male Population in Cameroon

Abstract: Introduction: According to WHO estimates, 57% of cases of liver cirrhosis and 78% of primary liver carcinoma are caused by a hepatitis B or C virus. This study aimed to assess the prevalence of these diseases and HIV among a young male population, according to region. Methods: This was a descriptive cross-sectional study conducted from 17 February to 31 March 2014 in the ten administrative regions of Cameroon. The study included male subjects of Cameroonian nationality aged at least 18 and at most 23, and livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…24 Also considering the fact that all participants who tested positive were unaware of their current infection status, the high prevalence rates in this study are particularly worrisome, as they suggest possible uncontrolled and unintended transmission from carriers to uninfected individuals within this community through multiple means of transmission. The seroprevalence of HBsAg rates found in this study concur with those of Noah et al, 25 who observed a rate of 22.8% for HBsAg in the farnorth region of Cameroon. Indeed, the seroprevalence of HBV is higher in the far-north region of Cameroon than in other regions of the country; other studies have reported prevalence rates of 11.8% for HBsAg and 0.6% for anti-HCV in the east, 26 4.1% for HBsAg and 0.4% for anti-HCV in the west, 27 10.1% for HBsAg and 4.8% for anti-HCV in the Littoral Region, 28 4.39%-12.14 % for HBsAg 29,30 and 1.44% for anti-HCV 30 in the center region, and 9.7% for HBsAg in the southwest region.…”
Section: Discussionsupporting
confidence: 92%
“…24 Also considering the fact that all participants who tested positive were unaware of their current infection status, the high prevalence rates in this study are particularly worrisome, as they suggest possible uncontrolled and unintended transmission from carriers to uninfected individuals within this community through multiple means of transmission. The seroprevalence of HBsAg rates found in this study concur with those of Noah et al, 25 who observed a rate of 22.8% for HBsAg in the farnorth region of Cameroon. Indeed, the seroprevalence of HBV is higher in the far-north region of Cameroon than in other regions of the country; other studies have reported prevalence rates of 11.8% for HBsAg and 0.6% for anti-HCV in the east, 26 4.1% for HBsAg and 0.4% for anti-HCV in the west, 27 10.1% for HBsAg and 4.8% for anti-HCV in the Littoral Region, 28 4.39%-12.14 % for HBsAg 29,30 and 1.44% for anti-HCV 30 in the center region, and 9.7% for HBsAg in the southwest region.…”
Section: Discussionsupporting
confidence: 92%
“… 60 65 Eight studies were conducted solely in rural areas, 13 41 48 58 67 22 in urban areas only, 33 36 40 43 44 46 47 49 50 52–57 62–64 66 and 14 in both urban and rural. 31 32 35 37 38 42 51 52 59–61 65 One study included only men, 57 11 only women 13 31 32 34 35 37 39 44 48 52 58 and 32 both sexes. 33 36 38 40–43 45–47 49–51 53–56 59–68 Concerning diagnostic test used in studies, 22 were a rapid diagnostic test, 13 32–36 38 40 45 48 49 53 54 56 58 59 61 62 65–67 9 were an enzyme linked immunoassay test, 37 41–44 47 52 57 64 5were enzyme immunoassay test, 31 39 46 60 63 1 was a chemiluminescent microparticle immunoassay and 7 studies not described in detail diagnostic tests.…”
Section: Resultsmentioning
confidence: 99%
“…This was done in one study but limited to young men (18–23 years). 57 In addition, the review included only one study specific to children. Across studies, HBV screening tools and their sensitivity and specificity may be different; this may influence estimates.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to find a Cameroonian study [7] in 2018 which presented similar results highlighting a low level of global knowledge as well as a study in California in the United States of America [9] 1997 which reported a low level of general knowledge with regard to hepatitis B. With a prevalence of 10% in Cameroon [4,10] it will be expected that Cameroonian healthcare personnel will be more intellectually equipped regarding hepatitis B in order to effectively fight against this scourge.…”
Section: Level Of Knowledgementioning
confidence: 54%
“…Geographically, there are high prevalence areas where it varies between 10% to 20% [3]. In Cameroon, in particular, the prevalence is estimated at 10% in the general population and 7.1% in pregnant women [4]. Vertical mother-to-child transmission is the most used contamination route in high endemic areas (Cameroon) [2,3,5].…”
Section: Introductionmentioning
confidence: 99%